Time to Transition: Barriers and Opportunities to Farmer Adoption of Soil GHG Mitigation Practices in Dutch Agriculture - Gomes, Anna; Reidsma, Pytrik (Frontiers in Sustainable Food Systems, 2021)
As the second largest exporter of agricultural products worldwide, the Netherlands is a production hub, a leading example of high yields per hectare. However, this productivity includes intensive farming practices, placing a risk on the climate through the emission of greenhouse gases N2O and CO2 from soil. To meet global efforts, the Netherlands must reduce its climatic impact, including soil emissions, but the transition to alternative farming practices can be challenging. This research identifies the barriers and opportunities for arable farmers to adopt practices which mitigate emissions from agricultural soils, and consists of a literature review, informant interviews, and semi-structured interviews with farmers, policy-makers, and boundary organizations. Main findings are (1) a lack of awareness by farmers of their soil greenhouse gas production, and (2) six barriers and five opportunities for farmer adoption with placement of these findings into different steps of adoption. Critical barriers include economic challenges, personal mindset, on-farm complications, and the need to reconcile different stakeholders’ rates of adoption. Opportunities lie with farmers becoming interested and able to quantify soil health, positive framing in the media, and policies or economic mechanisms to assist farmers. If the Netherlands can transition its farming system, the opportunities for the global food system could be significant.